The potential of buffalo as a meat producer - Néstor Simón Montiel-Urdaneta (Revista Científica)
The buffalo should not only be recognized for its good production of milk and dairy products. They should also be appreciated for converting forage into quality meat and their use as a work animal. To evaluate the potential of the buffalo as a meat-producing animal, 181 Murrah buffaloes weaned between 9 and 9.5 months of age with an average of 188 ± 10 kg (minimum 175, maximum 198) and a coefficient of variation (CV) of 5.32% were evaluated. From birth to weaning, they were fed under the Voisin grazing (Vg) modality with a single milking (from their mothers) receiving the milk produced from the right anterior teat until four months of age, and later, they only received the draining of the udder of the buffalo once the milking was concluded. After weaning, their feeding was at Vg without the supply of concentrated feed and ad libitum mineral supplement. They were weighed with 18 hours of fasting every 14 days during the 15.5 months of fattening. The weighing was performed with a digital scale without decimals and calibrated every ten weighings. PROC MEANS was used to calculate descriptive statistics, and a correlation analysis was performed between weaning weight and slaughter weight using the statistical package SAS version 9.1. The average gain was 285 ± 14.3 kg and CV 5.02% (weaning to slaughter). The total fattening and fattening period was 15.5 months (472 days); the average slaughter weight was 473 ± 17.5 kg and CV of 3.69% (minimum 450, maximum 496 kg) at 25 months of age. The average gain/day was 0.604 ± 0.048 g/day, with a CV of 7.94%. Weight loss from farm to slaughter was 10.62 ±  0.65 kg with a CV of 6.12%. The average weight of the hot carcass (HC) was 240.86 ± 6.77 kg with a CV of 2.82%. The yield in HC was 50.92% (minimum 49.96 and maximum 52.33%). Out of the 181 buffaloes, 12 were selected with an average slaughter weight of 460 kg, and the body weight distribution was evaluated: head: 17.38 kg; blood: 11.8 kg; skin: 46.68 kg; tail and ears: 3.72 kg; feet: 8.41 kg; meat: 182.15 kg; red and white bone: 73.29; white viscera: 30.26; red viscera: 21.79; fat: 24.30 and gastrointestinal contents: 40.22 kg. This group of buffaloes averaged 236.90 kg in HC with a 51.5% yield. No correlation was observed between weaning weight and slaughter weight. It can be concluded that the buffalo has an excellent meat yield, 39.59% of meat concerning live weight.